2022
DOI: 10.3390/computation10120207
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Static and Dynamic Behaviors of a Large Heavy-Duty Lathe Machine under Rated Loads

Abstract: The static and dynamic performances of a machine tool structure are considered to constitute the primary factors affecting the load-carrying capacity, geometric accuracy and surface precision of the workpiece. The machining performance of a large machine tool under stable conditions is effectively determined by its dynamic response to the cutting force at low-frequency excitation. This study, therefore, investigated the static and dynamic characteristics of a large heavy-duty lathe machine tool in which the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, the amplitude of the FRF is noticeably higher than that of modern Computer Numerical Control (CNC) machines. Indeed, references [9]- [11] all present machines with tool-point FRFs that have maximums lower than 0.17 µm/N. The present machine resembles another mobile machine tool presented in [1], [2] which has a flexibility value of 0.3 µm/N.…”
Section: Test Bench Descriptionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the amplitude of the FRF is noticeably higher than that of modern Computer Numerical Control (CNC) machines. Indeed, references [9]- [11] all present machines with tool-point FRFs that have maximums lower than 0.17 µm/N. The present machine resembles another mobile machine tool presented in [1], [2] which has a flexibility value of 0.3 µm/N.…”
Section: Test Bench Descriptionmentioning
confidence: 91%
“…However, the amplitude of the FRF is noticeably higher than that of modern Computer Numerical Control (CNC) machines. Indeed, references[9]-[11] all present machines with tool-point FRFs…”
mentioning
confidence: 99%
“…When subjected to complicated external dynamic loads, joint component substructures are prone to micro-vibration with multi-directional degrees of freedom (DOFs). The joints will be able to show off the crucial characteristic of flexible connections by storing and dissipating energy and demonstrating elasticity and damping [57][58][59]. Statistics indicated that joint factors like damping and stiffness account for 30% to 50% of stiffness and 90% of the CNCMT's dynamic performance damping.…”
Section: Major Identification Elementmentioning
confidence: 99%
“…When there is no tracking error in the servo axes, the multi-axis servo system will not exhibit a contour error. This is due to the fact that the tracking error is mainly affected by the closed-loop control and the hardware/machining conditions such as the static stiffness and the dynamic behaviour of the servo system [6]. In order to study the dynamic servo error of a machine tool, it is first necessary to develop a model of the servo feed system for each motion axis, primarily by modelling the servo drive system and the mechanical transmission system, and then to analyse the resulting characteristics of the servo axis with different factors, and the contour error in multi-axis coordinated motion.…”
Section: Introductionmentioning
confidence: 99%